Intensive pharmacovigilance of Heberprot-P® in patients with diabetic foot ulcer - Annavely González Ocaña; Ana María Ramos Cedeño; Yeny Dueñas Pérez; Francisco Carlos Valladares Más; Yahima Arrechea Betancourt (Medisur)
Foundation: Intensive pharmacovigilance is an effective tool to detect adverse reactions in relatively new drugs that have sanitary registration by a regulatory agency. Objective: to describe the adverse reactions of Heberprot-P® in patients with diabetic foot ulcer. Methods: descriptive, prospective, intensive pharmacovigilance study, carried out in the Dr. Gustavo Aldereguía Lima Hospital’s Angiology service, Cienfuegos, in 2022. This included 170 patients with diagnostic criteria for diabetic foot ulcer, treated with at least one dose of Heberprot-P®. In addition to sociodemographic variables, the type of adverse event, intensity, severity and causality were analyzed. Results: Patients with white skin color and over 60 years of age predominated. There were 210 adverse events, which were most frequently manifested by burning and pain at the injection site, tremor and chills, especially of mild intensity (61.4%) and with a probable causal relationship (76.6%). Conclusions: Despite being a safe drug, more pharmacovigilance studies related to Heberprot-P® should be carried out, since all marketed drugs require continuous monitoring.